2020
DOI: 10.1002/brb3.1926
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive frailty as a predictor of adverse outcomes among older adults: A systematic review and meta‐analysis

Abstract: Objective A systematic review and meta‐analysis basing on the prospective cohort studies were conducted to explore the risk of all‐cause mortality and dementia in cognitively frail older adults compared to robust older adults and to determine whether it was a predictor of adverse outcomes. Methods Pubmed, Web of Science, The Cochrane Library, EMBASE, and CINAHL databases were searched to retrieve studies on adverse outcomes of cognitive frailty. Two reviewers independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 42 publications
6
81
0
Order By: Relevance
“…For instance, the AUC of CI-PF and FI for mortality prediction in CHARLS were 0.563 and 0.573, respectively, which were relatively higher than that of the MCR measurement (i.e., 0.507). Recent meta-analyses revealed that vulnerable persons defined by CI-PF or FI in older persons have a higher risk of all-cause mortality [40, 41]. Our study extends the findings of these previous studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, the AUC of CI-PF and FI for mortality prediction in CHARLS were 0.563 and 0.573, respectively, which were relatively higher than that of the MCR measurement (i.e., 0.507). Recent meta-analyses revealed that vulnerable persons defined by CI-PF or FI in older persons have a higher risk of all-cause mortality [40, 41]. Our study extends the findings of these previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…During the 1999-2002 cycle, NHANES used the Digit Symbol Substitution Test (DSST) to assess cognitive function, with higher scores indicating better cognitive function (range: 0-133). According to the literature [23], a person was classified as having cognitive impairment if the summary score was below the median DSST score (i.e., 40).…”
Section: Cognitive Functionmentioning
confidence: 99%
“…CF is a type of frailty in patients who do not have dementia but have physical frailty (PF) and mild cognitive impairment (MCI) [4]. Researchers have found that, compared with the consideration of frailty and cognitive impairment, the consideration of CF can improve the prediction of disability, falls, dysfunction and death in the aging population [5][6][7][8][9]. CF is reversible, so it may become a target for the prevention of disability [10].…”
Section: Introductionmentioning
confidence: 99%
“…Prefrailty is a risk factor for cognitive dysfunction, and cognition tends to decline as frailty increases [ 24 27 ]. A meta-analysis from Bu [ 28 ] summarized that cognitive frailty was found to be a predictor of dementia in older adults living in communities. In our work, the abilities of memory, expression and solving problems were representative of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%